Something Good Out of the Bad Times? Intergenerational Inequalities in College Enrollment during the Great Recession in the United States - Pöyliö Heta (Turku Center for Welfare Research, 2022)
During times when labor market opportunities are few, the opportunity cost and risks of education diminish, resulting in an increase in educational enrollment. Although this holds for the entire population, there is a more steady increase in immediate college enrollment after high school over time, regardless of the impact of the Great Recession. Simultaneously, the net costs of education have grown, increasing the importance of families’ resources. This research examines whether the Great Recession has resulted in differences in socioeconomic inequalities in college enrollment in the United States. The results of the analysis of 2006-2013 high school graduation cohorts with data from the Panel Study on Income Dynamics show that female graduates from low-income families were more sensitive to changes in opportunity costs, evidenced by their increasing college enrollment, whereas male graduates whose parents held a college degree decreased their enrollment. Furthermore, the increase in enrollment, regardless of family background, was associated with the volume of the change in unemployment. Therefore, in addition to the tremendous negative impacts the Great Recession had on families and individuals, it had a positive influence on intergenerational inequalities in college enrollment, particularly benefiting disadvantaged families.